Multiscale theory and simulation of plasmon‐enhanced molecular optical processes. Issue 21 (17th May 2014) - Masiello, David J.
<x xml:space="preserve">Abstract</x> Theoretical descriptions of molecular optical processes occurring in the presence of a surface plasmon resonance are surveyed in this Perspective. Particular emphasis is placed on semiclassical approaches that blend together first principles molecular quantum mechanics with the full‐wave continuum electrodynamics of the molecule's nanoplasmonic environment. It is demonstrated how the latter can be built into the former through many‐electron Green's function techniques combined with numerical values of the plasmon's locally scattered field. The effects of the plasmon on the molecule's one‐body and many‐body electronic structure is described in detail and several open theoretical challenges are discussed. © 2014 Wiley Periodicals, Inc.